Pengujian Ketentuan Penghapusan Norma dalam Undang-Undang - Ali Safa’at, Muchamad (Mahkamah Konstitusi Republik Indonesia, 2010)
Theoretically and practically (judicial review), include two types, namely formal verification (formale toetsingrecht) and material verification (materielle toetsingrecht). The formal verification is an authority of assessing whether or not a legislative product is produced in accordance with the prevailing procedures. While a material verification is an authority to examine and measure whether or not a legal regulation contradicts with a higher level regulation, as well as whether or not an authority has the right to establish a certain regulation. Article 51 paragraph (3) of Law Number 24 Year 2003 regarding Constitutional Court state about it. In this context, material verification include extensive material, ie the whole matter of law, in part, or a small part of a word or even punctuation that can affect the norm. Thus, the provisions not only affect the meaning, but even the existence of a norm should be examined by the Constitutional Court. In addition, the loss of norms can violate constitutional the rights of citizens’.